2018
DOI: 10.1007/s00431-018-3268-x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of pulse oximetry screening for critical congenital heart defects following homebirth and early discharge

Abstract: Pulse oximetry (PO) screening is used to screen newborns for critical congenital heart defects (CCHD). Analyses performed in hospital settings suggest that PO screening is cost-effective. We assessed the costs and cost-effectiveness of PO screening in the Dutch perinatal care setting, with home births and early postnatal discharge, compared to a situation without PO screening. Data from a prospective accuracy study with 23,959 infants in the Netherlands were combined with a time and motion study and supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 26 publications
1
15
0
7
Order By: Relevance
“…After duplicate removals, 716 articles were considered eligible for screening by title and abstract. After full-text screening, 35 articles were included for the final assessment (see Appendix C for the PRISMA flow diagram) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. No additional studies were found on the websites of the INAHTA HTA agencies.…”
Section: Resultsmentioning
confidence: 99%
“…After duplicate removals, 716 articles were considered eligible for screening by title and abstract. After full-text screening, 35 articles were included for the final assessment (see Appendix C for the PRISMA flow diagram) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. No additional studies were found on the websites of the INAHTA HTA agencies.…”
Section: Resultsmentioning
confidence: 99%
“…Diversos fatores estão envolvidos na prevalência das AC, de um modo geral nesta amostra foram captadas maior quantitativo de publicações que abordaram as AC do sistema cardiovascular e respiratório (14,16,(19)(20)(21)(22)(23)(24)(25)28,29,33,38,(40)(41) . Esclarece-se que estas são complexas e demandam de exame de imagem para o diagnóstico, podendo impactar nas altas taxas de mortalidade (2) .…”
Section: Discussionunclassified
“…Quanto à população, o maior volume dos estudos incluiu crianças menores de um ano (13,15,17,18,23,25,29,33,(38)(39)(40)(41) . Cenário este que pode ser advindo do fato de as AC graves serem incompatíveis com a vida, assumindo papel crescentemente expressivo na morbimortalidade infantil, sobretudo no período neonatal (3) .…”
Section: Discussionunclassified
See 2 more Smart Citations